Maternal high-fat diet increases the susceptibility of offspring to colorectal cancer via the activation of intestinal inflammation - Zheng, Shimin; Yin, Jianbin; Yue, Hui; Li, Lifu (Frontiers in Nutrition, 2023)
A high-fat diet plays a key role in the pathogenesis of colorectal cancer, and this effect on the gut can also occur in the offspring of mothers with a high-fat diet. In this review, we discuss the role of a high-fat diet in the pathogenesis of colorectal cancer and summarize the effects of a maternal high-fat diet on the activation of inflammation and development of colorectal cancer in offspring. Studies have found that a maternal high-fat diet primarily induces an inflammatory response in the colorectal tissue of both the mother herself and the offspring during pregnancy. This leads to the accumulation of inflammatory cells in the colorectal tissue and the release of inflammatory cytokines, which further activate the NF-κb and related inflammatory signaling pathways. Research suggests that high levels of lipids and inflammatory factors from mothers with a high-fat diet are passed to the offspring through the transplacental route, which induces colorectal inflammation, impairs the intestinal microecological structure and the intestinal barrier, and interferes with intestinal development in the offspring. This in turn activates the NF-κb and related signaling pathways, which further aggravates intestinal inflammation. This process of continuous inflammatory stimulation and repair may promote the uncontrolled proliferation of colorectal mucosal cells in the offspring, thus increasing their susceptibility to colorectal cancer.